2021
DOI: 10.1002/slct.202102942
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Substituent Effects in the Stereochemistry of [3+2] Cycloaddition Reactions of Aryl‐ and Alkyldiazomethylphosphonates with Norbornadiene within a MEDT Perspective

Abstract: The [3 + 2] cycloaddition (32CA) reactions of norbornadiene with aryl and alkyl substituted diazomethylphosphonates (SDAPs) have been studied within the molecular electron density theory (MEDT). Electron localization function (ELF) shows the presence of a pseudoradical C3 center at the alkyl SDAPs, classifying them as pseudo(mono)radical species, while the aryl SDAP is classified as a zwitterionic one, owing to the delocalization of the C3 electron density on the C3-P bond. These 32CA reactions present high ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Additionally, the stepwise 32CA mechanism 27 is also well known in nitrone chemistry. MEDT has been successfully applied to study various aspects of 32CA reactions in the last six years, such as strain promotion, 28,29 regioselectivity, 30 influence of catalysts, 31,32 chemoselectivity, 33,34 stereoselectivity, 33,35 substituent effects, 36,37 etc. In 2018, Domingo et al 38 reported the MEDT study to analyze the fused regioselectivity in the IM32CA reactions of cyclic nitrones.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the stepwise 32CA mechanism 27 is also well known in nitrone chemistry. MEDT has been successfully applied to study various aspects of 32CA reactions in the last six years, such as strain promotion, 28,29 regioselectivity, 30 influence of catalysts, 31,32 chemoselectivity, 33,34 stereoselectivity, 33,35 substituent effects, 36,37 etc. In 2018, Domingo et al 38 reported the MEDT study to analyze the fused regioselectivity in the IM32CA reactions of cyclic nitrones.…”
Section: Introductionmentioning
confidence: 99%
“…15 Thus, while pdr-type 32CA reactions take place very easily, zw-type 32CA reactions demand suitable nucleophilic/electrophilic activations. Regio, 16,17 stereo, 17–19 and chemoselectivity, 20,21 catalysis, 22,23 strain promotion, 24,25 substituent effects, 26,27 unexpected reactivity 28 and other aspects of chemical reactions have been successfully analyzed using the MEDT framework.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Domingo proposed the molecular electron density theory [8] (MEDT) to establish the role of electron density changes on molecular reactivity. Since last seven years, the MEDT perspective has been successfully applied to analyse the experimentally observed region [9,10], stereo- [9][10][11][12] and chemoselectivity [13,14], reactivity [15][16][17], substituent effects [18,19], catalysis [20,21], strain promotion [22,23] and several other aspects of 32CA reactions [24,25]. Recently, we have reported the MEDT analysis of the chemo and regioselectivity observed in the 32CA reaction of 4-chlorobenzonitrile N-oxide and β-aminocinnamonitrile for construction of 1,2,4oxadiazoles [26].…”
Section: Introductionmentioning
confidence: 99%